Promotion of dental and oral health for school dental health program teachers at elementary school level in the Sukoharjo Regency - Dendy Murdiyanto; Ariyani Faizah; Nilasary Rochmanita Suparno; Septriyani Kaswindiarti; Juwita Raditya Ningsih; Dwi Kurniawati (Universitas Muhammadiyah Magelang, 2023)
The role of teachers is crucial for the success of oral health promotion because schools are environments equipped with resources to teach how to maintain healthy teeth and mouth. This activity aims to enhance the knowledge and skills of UKGS teachers in the Sukoharjo Regency area. The methods employed include lectures, discussions, and demonstrations by the facilitator, followed by re-demonstrations by the participants for evaluation. Knowledge was assessed using a questionnaire administered before and after the training. The evaluation results indicate a t-test significance value of 0.000 with p ≤ 0.05, suggesting an improvement in the understanding and knowledge of elementary school UKGS teachers after attending the training.